EVALUATION OF ANTIOXIDANT POTENTIAL AND QUANTITATIVE ESTIMATION OF PHENOLIC AND FLAVONOID CONTENT IN SOME SELECTED NEPALESE MEDICINAL PLANTS - KHAREL, RUPAK; RAJ SHARMA, KHAGA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The aim of this study is to evaluate the antioxidant potential, determination of total phenolic and flavonoid content in nine selected medicinal plants Spondias pinnata, Melia azedarach, Ageratina adenophora, Urtica dioica, Curcuma longa, Bauhinia variegata, Elaeocarpus angustifolius Blume, Achyranthes aspera, and Psidium guajava from Kavre district of Nepal using in vitro studies. Methods: Methanolic plant extracts were prepared by cold percolation method. The methanol extract of nine medicinal plants collected from Kavre district of Nepal, was screened for assessing bioactive phytoconstituents followed by antioxidant property, total phenolic, and flavonoid content. Different plants collected were powdered and extracted with methanol, concentrated by a rotatory evaporator and analyzed for the presence of phytochemicals. The antioxidant potential of the plant extracts was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Results: The phytochemical analysis of methanolic extracts of all nine medicinal plants displayed the presence of various secondary metabolites such as alkaloids, flavonoids, polyphenols, saponins, and quinones. The extract of S. pinnata showed the highest percentage of radical scavenging activity up to 87.94±1.88 with 50% inhibitory concentration (IC50) 17.51±1.27 μg/mL, followed by B. variegata, 80.63±1.06 with IC50 value 26.55±2.61 μg/mL. The standard, ascorbic acid has IC50 value of 20.13±1.17 μg/mL. Further, the ethyl acetate fraction of S. pinnata showed the maximum percentage of radical scavenging (85.92±1.37) with IC50 value of 46.95±1.17 μg/mL. Moreover, S. pinnata displayed the highest total phenolic content (TPC) 48.26±1.23 mg GAE/g (milligram gallic acid equivalent per gram) extract while the highest flavonoid content was displayed by Melia azedarach 41.07±1.53 mg QE/g (milligram quercetin equivalent per gram) extract measured by the Folin–Ciocalteu reagent method and aluminum chloride colorimetric method. Conclusions: The preliminary results of this study have put forward the extract of S. pinnata showed the highest percentage of radical scavenging activity and S. pinnata displayed the highest TPC while the highest flavonoid content was displayed by Melia azedarach methanolic extracts although the further studies are needed to assess its mechanism of action.